PENANGANAN TINDAK PIDANA ABORSI OLEH KEPOLISIAN SEKTOR BELIMBING RESOR MELAWI - Gadion SH (Universitas Kapuas Sintang, 2022)
The police are known as the officialpunishment of abortion crime and promiscuity are everywhere on teenager. Therefore,organization that is responsible for protecting people and property. In this case, police resort faces the difficulties in handling abortion crime. the difficulties are coming from the unmanageable evidence and the lack awareness of people who expected to help police proving the evidence. this research is designed as a form of juridical sociological approach based on law and fact. a descriptive analysis is used as technique for analysis of this research. This analysis is important to describe a problem systematically. Due to the role of police who responsible for protecting people and property, it is crucial for police for investigating and solving crime, and catching people who have committed a crime especially on the case of abortion crime. in other hand, police are found the shortcoming, namely: It is difficult to consider the appropriate regulation foritisveryrecommendedtorevisetheregulationofKUHP who stand for abortion crime. Key words: The Handling of Abortion Crime